Association between dialysis dose and biochemical blood parameters - Nur Zakiah Mohd. Saat; Sazlina Kamaralzaman; Norshafarina Shaari; Farida Zuraina Mohd. Yusoff (Universiti Kebangsaan Malaysia, 2011)
The end stage renal disease (ESRD) patients requires hemodialysis to survive. Efficacy of the treatment is determined by evaluation of minimal dialysis dose (Kt/V) which is 1.2. A cross sectional study was conducted among patients that undergo hemodialysis in a dialysis centre in Kuala Lumpur, Malaysia. The objectives of the study were to determine the association between dialysis dose and demographic factors and assessed the association between biochemical blood parameter and the demographic factors. The biochemical blood parameters were serum albumin, creatinine, cholesterol and hemoglobin. Result showed that all Indians and 54% of Chinese patients achieved the required dialysis dose. However only 29% of Malay patients attained the effective dialysis dose. More women patients accomplished the dialysis dose of at least 1.2 compared to men patients with odd ratio of 11.24. All the biochemical blood parameters were independent of the demographic factors. However, the cholesterol level was associated significantly with gender (p<0.05). In conclusion, the study found the biochemical blood parameter and dialysis dose were not influenced by the demographic factors.